2015
DOI: 10.1016/j.nlm.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multi-innervated dendritic spines as a novel mechanism of long-term memory formation

Abstract: NMDA receptor-dependent long-term potentiation (LTP) at hippocampal CA1 synapses is a well-accepted mechanism underlying long-term memory (LTM) formation. However, studies with mice that lack threonine-286 autophosphorylation of αCaMKII have shown that hippocampal LTM can be formed despite absence of NMDA receptor-dependent CA1 LTP. After multiple training trials, LTM formation in these mutants is linked to the generation of multi-innervated dendritic spines (MIS), a spine that receives typically two presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…These pathologies contribute to the final outcome of neuronal and synaptic death . However, synaptic linkage is the foundation of information transmission between neurons at the distal ends of dendrites, and changes to this transmission play an important role in memory . Furthermore, learning and memory impairment observed in AD has a close relationship with hippocampal synaptic damage in its early stage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathologies contribute to the final outcome of neuronal and synaptic death . However, synaptic linkage is the foundation of information transmission between neurons at the distal ends of dendrites, and changes to this transmission play an important role in memory . Furthermore, learning and memory impairment observed in AD has a close relationship with hippocampal synaptic damage in its early stage .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] However, synaptic linkage is the foundation of information transmission between neurons at the distal ends of dendrites, and changes to this transmission play an important role in memory. 10,11 Furthermore, learning and memory impairment observed in AD has a close relationship with hippocampal synaptic damage in its early stage. 12,13 Developmentally regulated brain protein (abbreviated as Drebrin or Dbn, also known as Dbn1 in mouse)…”
mentioning
confidence: 99%
“…We observed a few spines containing segmented PSDs are innervated by multiple presynaptic boutons. An increase of multi-innervated spines has been reported to be associated with LTP (Giese et al, 2015;Nikonenko et al, 2003;Radwanska et al, 2011). However, probably due to the rare existence of multi-innervated spines (~1% of total spines), it is seldom reported in previous population EM studies that analyzed the ultrastructural correlates for LTP.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that LTP is correlated with, on average, an enlargement in spine and PSD size, a higher number of concave spine profiles, an increase in perforated PSD, and an increase in polyribosome containing spines (Desmond and Levy, 1986;Van Harreveld and Fifkova, 1975;Harris et al, 1992;Ostroff et al, 2002). Furthermore, LTP has been associated with generation of multi-innervating spines and boutons (Giese et al, 2015;Toni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The basic unit of information transmission between neurons is the synapse, which is composed of dendritic spines on the surface of dendrites and plays an important role in learning and memory [1,2]. The developmentally regulated brain protein drebrin (Dbn) contains adult type (Dbn A) and embryonic type (Dbn E) [3,4], distributed widely in the central nervous system and peripheral tissue.…”
Section: Introductionmentioning
confidence: 99%